The Effect of Lubrication Agent in Fabrication of Recycled Steel Powder using Ball Milling from Machining Steel Chips - Mohd Fitri Mohamad Wahid; C.H. Shun; Shaiful Rizam Shamsudin; Ruhiyuddin Mohd Zaki (Universiti Malaysia Perlis (UniMAP), 2008)
Organized by Universiti Malaysia Perlis (UniMAP), 9th - 12th June 2007 at Park Royal Hotel, Penang.